Identity Politics and Separatist Movement in Post-colonial Sub-Saharan Africa: The Case of the Nigeria State (2015-2021) - Obiefule, Oguchukwu Temple; Saibu, Israel Abayomi; Akerele, Emmanuel Wasiu (NIU Journal of Social Sciences, 2023)
The Nigeria State had fought a gruesome war to keep the country one from a separatist movement in the 1960s shortly after its independence. In Over sixty (60) years of post-independence, the separatist movement demanding for an independent state of Biafra has not faded with the passing of time, rather, it re-emerged in a new cast called the Indigenous People of Biafra (IPOB) with membership in diaspora and at home. Even when the Nigerian government had proscribed the group and labeled it as a terrorist organization, the group may have employed the nuances of globalization and social media in registering their presence and attacking the government of the day. This study seeks to interrogate the socio-political dynamic of identity politics that has shaped and sustained the agitation for an independent Biafran state from the sovereign Nigerian state for over five decades. The study employed ethnography, qualitative data and content analysis in its methodology. This work argues that identity politics along religious and ethnic lines has sustained the call for the Biafran nation in the post-colonial Nigerian state.  The study concludes that the Nigerian state is politically bifurcated along ethnic and religious lines and these have sustained the perennial call for a sovereign Biafran State. The study suggests that structural imbalances within the Nigerian state should be properly addressed to reflect equity, justice and fairness among the components units that constitutes the Nigerian state  Keywords: Identity Politics, Biafra, Agitation, Separatist Movement and Post-Colonial Africa.